PRARANCANGAN PABRIK PARAXYLENE DENGAN PROSES DISPROPORSIONASI TOLUENE KAPASITAS 350.000TON/TAHUN - Listiani, Listiani, Dr.Ir. Ahmad M Fuad, M.T., Ph.D, Ir. Herry Purnama, M.T., Ph.D (2017)
Abstract Paraxylene can be used as a raw material dimetyl terephtalate and terephtalate acid. The capacity of the plant to be established is 350,000 tonnes / year beroprasi for 330 days per year and is continuous. The planned factory was established in 2020 in Cilegon, Banten. Total labor requirement is 164 people. Raw material for making paraxylene is toluene and hydrogen with the aid of a catalyst ZSM-05 at 400-450⁰C temperature and pressure of 30 atm. The reactor used is a fixed bed multitube non-isothermal adiabatic. Conversion to 31% of this reaction is endothermic. Necessary stage is the stage of storage of raw materials, preparation of raw materials and product formation stage. Purity required is 95%. Phase happens is the gas phase. The first phase toluene vaporized liquid to a gas is reacted with hydrogen with a catalyst ZSM-5. The reaction temperature is 450⁰C. The process produces paraxylene main products and byproducts such as benzene. Cooling water used comes from rivers Ciujung. Paraxylene factory is a limited liability company held by some shareholders. The factory was built on land with an area of 3,800 m2. Working capital needed is Rp 142.200.962.196,00.Percent return on investmen before tax is 68.07% and after tax to 51.05%. Pay out time before tax after tax of 1.3 years and 1.6 years. Break even point of 42.31% and shut down Point amounted to 25.15%.